A competition‐based explanation of collaborative invention within the firm. (22nd March 2013) - Toh, Puay Khoon; Polidoro, Francisco
<x xml:space="preserve">Abstract</x> Existing literature shows that collaborative invention within the firm enhances innovativeness by facilitating knowledge recombination. Despite such benefit, firms vary in their use of collaborative invention when drawing on their individual inventors' knowledge. In addressing this puzzle, we argue that competition from rival products building on similar knowledge compels firms to favor search depth over exploratory search and respond expeditiously, thus reducing a firm's inclination toward collaborative invention. In contrast with prior research's focus on how upstream resources influence a firm's position in downstream markets, this study shows that downstream competition drives heterogeneity across firms in their utilization of upstream resources. Copyright © 2013 John Wiley & Sons, Ltd.